VIRTUAL ASSETS AND DIGITAL CONTENT AS AN OBJECT OF CIVIL LAW - Tetiana Fedorenko; Serhii Sadkovskyi (International Journal of Innovative Technologies in Social Science, 2023)
This article summarizes the concept of "virtual assets" in the global context. It is noted that the formation of the virtual asset market in Ukraine began with the popularization of cryptocurrencies in 2013. It was determined that the potential of Ukraine, as one of the leading countries in the field of virtual assets, is huge. Two draft laws submitted to the Verkhovna Rada were analyzed, according to which virtual assets and digital content belong to the objects of civil law and are subject to the regulations of the Civil Code. It is noted that on December 17, 2022, draft Law No. 6447 was registered in the Verkhovna Rada. This draft law provides for amendments to be made to the Civil Code, in particular, Articles 115, 177, 179, which define, among other objects of civil rights, digital things, their essence as subject of the digital environment, which is in circulation only in digital form, and in respect of which civil rights and obligations may arise, as well as the circle of digital things, which are virtual assets, is outlined. It is characterized that the provisions of the related draft law No. 6576 define the sphere of civil legal relations, distinguish subjective and objective criteria for compliance of digital content (services) with the terms of the concluded contract, establish the legal consequences of non-provision of digital content (services) under the contract, as well as non-compliance of content (services).